An Osteopontin-Integrin Interaction Plays a Critical Role in Directing Adipogenesis and Osteogenesis by Mesenchymal Stem Cells. (13th January 2014) - Chen, Qing; Shou, Peishun; Zhang, Liying; Xu, Chunliang; Zheng, Chunxing; Han, Yanyan; Li, Wenzhao; Huang, Yin; Zhang, Xiaoren; Shao, Changshun; Roberts, Arthur I.; Rabson, Arnold B.; et al.
Abstract : An imbalance between normal adipogenesis and osteogenesis by mesenchymal stem cells (MSCs) has been shown to be related to various human metabolic diseases, such as obesity and osteoporosis; however, the underlying mechanisms remain elusive. We found that the interaction between osteopontin (OPN), an arginine-glycine-aspartate-containing glycoprotein, and integrin αv/β1 plays a critical role in the lineage determination of MSCs. Although OPN is a well-established marker during osteogenesis, its role in MSC differentiation is still unknown. Our study reveals that blockade of OPN function promoted robust adipogenic differentiation, while inhibiting osteogenic differentiation. Re-expression of OPN restored a normal balance between adipogenesis and osteogenesis in OPN −/− MSCs. Retarded bone formation by OPN −/− MSCs was also verified by in vivo implantation with hydroxyapatite-tricalcium phosphate, a bone-forming matrix. The role of extracellular OPN in MSC differentiation was further demonstrated by supplementation and neutralization of OPN. Blocking well-known OPN receptors integrin αv/β1 but not CD44 also affected MSC differentiation. Further studies revealed that OPN inhibits the C/EBPs signaling pathway through integrin αv/β1. Consistent with these in vitro results, OPN −/− mice had a higher fat to total body weight ratio than did wild-type mice. Therefore, our study demonstrates a novel role for OPN-integrin αv/β1 in regulating MSC differentiation. Stem Cells   2014;32:327–337